The impact of the world food price index on some East-European economies - Saman, Corina; Alexandri, Cecilia (Journal of Business Economics and Management, 2018)
This paper deals with the dynamic response of exchange rates, inflation and agricultural foreign trade in Bulgaria, Poland and Romania to global food prices. We employ time-varying VARs with stochastic volatility to estimate the behaviour of these macroeconomic variables over the 2001M1–2015M12 period. The original contribution of this paper is that it captures the time variation and nonlinearities of the relationship between variables taking into account food price volatility and its macroeconomic implications. The main findings of the paper are: (i) high global food prices were transmitted to domestic economies causing pressure on inflation in the long run; (ii) in the short run the impact of a positive shock in international food price increases domestic inflation, depreci-ates the currency and reduces the agricultural trade; (iii) the vulnerabilities to global food prices are more pregnant for Romania and Bulgaria; (iv) the difference in the transmission of world prices is related to the different status of the countries as regards food and agricultural trade. The findings of the research would be significant for the governments to promote policies to help farmers respond to the rising of food prices by growing more and responding to export opportunities that may arise.